Cross-cultural variations in motives and barriers for organic food consumption: a narrative review - Zidan, Souzan; Hilary, Serene; Platat, Carine (Frontiers in Sustainable Food Systems, 2025)
Current dietary practices significantly contribute to environmental degradation, with organic food consumption emerging as a viable alternative for promoting sustainability. This review explores the diverse motivations and barriers influencing organic food consumption, drawing comparisons between developing and developed countries. A systematic review of 67 peer-reviewed studies published after 2018 up to March 2025 was conducted, sourced from databases such as PubMed, Google Scholar, ScienceDirect, and Scopus. Of the included studies; 43 were from developing countries, 21 were from developed countries, and 3 offered comparative insights between organic food consumption patterns in developing and developed countries. The findings reveal that while health and environmental concerns are universal drivers for organic food consumption, significant differences exist in the specific motivations and barriers across regions. In developing countries, the high cost and limited availability of organic foods were identified as the primary barriers, whereas consumers in developed nations face skepticism toward certification and labeling systems. The influence of demographic factors such as age, income, and education varied, with younger consumers in developed countries showing a greater propensity for organic food consumption than their counterparts in developing nations. Moreover, social consciousness and ethical considerations were more pronounced in developed countries, highlighting a broader awareness of global environmental issues. This review highlights the need for targeted strategies to overcome barriers and promote organic food consumption globally, particularly in regions where the market is still emerging.